Multicultural Values in Islamic Education and Character Books for Class V Elementary School and Their Implementation at SDN 20 Kota Bima - Fathani Mubarak; Ruslan; Nasaruddin (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to construct the content of multicultural values ​​in the Islamic Education and Character books for class V elementary school in 2021 and their implementation at SDN 20 Kota Bima. The type of research used is qualitative research by combining two research designs, namely library research and field research. The data analysis techniques used for library research are content analysis and discourse analysis. Meanwhile, data collection for field research uses observation, interviews and documentation through interactive analysis techniques. The results of this research show that there are 162 values ​​identified as multicultural values ​​in the Islamic Religious Education and Character Education textbook for Class V Elementary School in 2021. The scope of these values ​​is described in visual and verbal form. The implementation of multicultural values ​​at SDN 20 Kota Bima is realized in the form of activities such as flag ceremonies every Monday, studying together every Wednesday in the hall of SDN 20 Kota Bima, eating together every Thursday, morning exercise and mutual cooperation every Saturday, participate in every MTQ parade and cultural parade, get used to the 5S culture (greeting, smile, greet, be polite and courteous), students are required to clean the classroom according to the picket schedule that has been made and agreed upon, and implement IMTAQ coaching through religious practices.